Combining resistance and aerobic training intensities: practical remarks - Sousa, A.; Neiva, H. P.; Gil, M. H.; Alves, A. R.; Fail, L. B.; Neves, P. P.; Marques, M. C.; Marinho, D. (Motricidade, 2019)
INTRODUCTION A combination of resistance and aerobic regimens, usually named as concurrent training (CT), has attracted strong attention from the scientific community in recent years due to its potential to simultaneously induce cardiorespiratory and neuromuscular gains (Joo, 2018). However, there is a lack of research consensus on this subject, and more specifically when related to some interreference effect that exist when combining different resistance and aerobic intensities (Cadore et al., 2012; Cadore et al., 2014; Garciìa-Pallareìs & Izquierdo, 2011). Thus, our aim was to provide a practical suggestion to improve athletes` performance on different sports by using a CT program design. METHODS A literature research was carried out using several databases (Web of Science, PubMed, ScienceDirect, Scholar Google, and Scopus) from January 1980 to September 2018, to identify studies related to CT with different intensities in young adults. The search was performed containing key terms such as "concurrent training", "intensities", and "young adults". The initial search identified 2469 initial studies. For the qualitative analysis, a total of 7 studies were considered relevant for a detailed analysis. RESULTS According to the existing literature, we suggest a CT program for 8 weeks, performed twice a week, including full squat (FS), counter-movement jump (CMJ), sprint and aerobic exercitation. FS training should consist on 3 sets of 5-8 repetitions with external loads from 70 to 85% of maximal repetition (1RM) with 3 minutes of rest between sets. After FS training, CMJs can be performed in a platform of 50 to 60 cm high (3 to 4 sets of 4 to 5 repetitions), to complete the resistance training (RT). Each RT session should last about 20 min, including the warm-up period. After the RT program and some rest (15min), an aerobic workout should be performed. This training component should be simple to evaluate and control in a real-context, perhaps consisting of 16-20 minutes of 20 m shuttle run exercise at 80% of maximal individual speed. Maximal aerobic speed should be previously evaluated during a 20m multistage shuttle run test. CONCLUSIONS CT have been shown beneficial effects on athletes` performance, once properly combined. The intensity of RT and/or AT seems to play an essential role for higher gains, with some major gains when combining higher RT intensities with lower AT intensities. Considering the literature findings, it was possible to suggest a CT program for 8-weeks duration to obtain maximal cardiorespiratory and strength gains.